60 Seconds to Survival: A Multisite Study of a Screen‐based Simulation to Improve Prehospital Providers Disaster Triage Skills. Issue 2 (31st January 2018) - Cicero, Mark X.; Whitfill, Travis; Walsh, Barbara; Diaz, Maria Carmen; Arteaga, Grace; Scherzer, Daniel J.; Goldberg, Scott; Madhok, Manu; Bowen, Angela; Paesano, Geno; Redlener, Michael; Munjal, Kevin; et al.
Abstract: Objectives: Paramedics and emergency medical technicians (EMTs) perform triage at disaster sites. There is a need for disaster triage training. Live simulation training is costly and difficult to deliver. Screen‐based simulations may overcome these training barriers. We hypothesized that a screen‐based simulation, 60 Seconds to Survival (60S), would be associated with in‐game improvements in triage accuracy. Methods: This was a prospective cohort study of a screen‐based simulation intervention, 60S. Participants included emergency medical services (EMS) personnel from 21 EMS agencies across 12 states. Participants performed assessments (e.g., check for pulse) and actions (e.g., reposition the airway) for 12 patients in each scenario and assigned color‐coded triage levels (red, yellow, green, or black) to each patient. Participants received on‐screen feedback about triage performance immediately after each scenario. A scoring system was designed to encourage accurate and timely triage decisions. Participants who played 60S included practicing EMTs, paramedics, and nurses as well as students studying to assume these roles. Participants played the game at least three times over 13 weeks. Results: In total, 2, 234 participants began game play and 739 completed the study and were included in the analysis. Overall, the median number of plays of the game was just above the threshold inclusion criteria (three or more plays) with a median of four plays during the study period (interquartile range [IQR] = 3–7). There was a significant difference in triage accuracy from the first play of the game to the last play of the game. Median baseline triage accuracy in the game was 89.7% (IQR = 82.1%–94.9%), which then increased to a median of 100% at the last game play (IQR = 87.5%–100.0%; p < 0.001). There was some variability in median triage accuracy on fourth through 11th game plays, ranging from 95% to 100%, and on the 12th to 16th plays, the median accuracy was sustained at 100%. There was a significant decrease in the rate of undertriage: from 10.3% (IQR = 5.1%–18.0%) to 0 (IQR = 0%–12.5%; p < 0.001). Conclusion: 60 Seconds to Survival is associated with improved in‐game triage accuracy. Further study of the correlation between in‐game triage accuracy and improvements in live simulation or real‐world triage decisions is warranted.